Doomscrolling and mental well-being among university students: A qualitative study of late-night digital behavior - Hengki Yandri; Deltia Ismanidar; Dosi Juliawati; Daflaini Daflaini; Rasmita Rasmita; Darsi Darsi; Yatti Fidya (Empathy : Jurnal Fakultas Psikologi, 2026)
Doomscrolling has evolved beyond a mere habit into a significant maladaptive behavior that systematically erodes the mental well-being of university students. This study explores the nexus between late-night compulsive content consumption and the degradation of psychological health. Employing a qualitative approach, the research focuses on seven purposively selected informants exhibiting extreme device usage (>5 hours/day). This sample size was intentionally curated to achieve phenomenological depth and data saturation, ensuring a rich, granular understanding of the digital experience that large-scale surveys often overlook. Data were gathered through participant observation and in-depth interviews, subsequently analyzed using thematic coding to identify recurring behavioral patterns. The findings reveal that informants spend 3 to 5 hours nightly in a "doomscrolling loop," driven by information anxiety and social pressure (oversharing). Rather than providing a digital escape, this activity consistently delays sleep, triggering emotional exhaustion and a sharp decline in morning cognitive focus. Critically, this study proves that doomscrolling serves as a failed coping mechanism that disrupts time management and psychological stability. These findings contribute to the global discourse on digital mental health by highlighting the urgent need for mindfulness-based digital literacy interventions to help students navigate the demands of a hyper-connected academic environment.